IMPOLITENESS STRATEGIES AND ITS SPEECH ACTS OF MAIN ANTAGONIST CHARACTER UTTERANCES IN CRUELLA MOVIE - Wildaan Mukhallad; Agung Prasetyo Wibowo (Journal of Language and Literature, 2022)
This research discusses impoliteness strategies and its speech acts of main antagonist utterances in Cruella movie. The objectives of this research are to find out the impoliteness strategies in the utterances of main antagonist in Cruella movie using Culpeper’s impoliteness strategies (1996) and to find out the speech acts in the impolite utterances of main antagonist in Cruella movie using Searle’s classification of speech acts (1979). The study adopted a descriptive qualitative method. The source of data of this research is a movie entitled Cruella. This research uses the dialogue script of Cruella movie as the data. The result shows that there are 90 data found in this research consisting of five impoliteness strategies and five kinds of speech acts in the utterances of main antagonist in Cruella movie. The impoliteness strategies found in this research are negative impoliteness with 49 data or 54%, positive impoliteness with 18 data or 20%, bald-on record impoliteness with 11 data or 12%, sarcasm or mock politeness with 8 data or 9%, and withhold politeness with 4 data or 4%. The kinds of speech acts found in this research are directive with 41 data or 46%, representative with 22 data or 24%, expressive with 21 data or 23%, commissive with 4 data or 4%, and declaration with 2 data 2%. The classification of speech acts found in the impoliteness strategies are directive in negative impoliteness with 30 data or 33%, expressive in negative impoliteness with 12 data or 13%, representative in positive impoliteness strategy with 8 data or 9%, representative acts in bald-on record impoliteness with 7 data or 8%, directive in positive impoliteness with 6 data or 7%, representative in negative impoliteness strategy with 4 data or 4%, expressive in sarcasm or mock politeness with 4 data or 4%, directive in bald-on record impoliteness with 4 data or 4%, commissive in negative impoliteness with 3 data or 3%, expressive in withhold politeness with 3 data or 3%, expressive in positive impoliteness with 2 data or 2%, declaration acts in positive impoliteness strategy with 2 data or 2%, representative in sarcasm or mock politeness strategy with 2 data or 2%, commissive in sarcasm or mock politeness with 1 datum or 1%, directive in sarcasm or mock politeness with 1 datum or 1%, and representative in withhold politeness with 1 datum or 1%. Based on the result of this research, directive speech act in negative impoliteness strategy is the most frequent utterances performed by the main antagonist in Cruella movie.